(untitled) (Bangladesh Journal of Nuclear Medicine, 2021)
Papillary and follicular thyroid carcinomas, together known as differentiated thyroid carcinomas (DTC), are among the most curable of cancers. Distant metastases are rare events at the onset of DTC. Sites of metastases from follicular thyroid cancer (FTC) are usually osseous, and those from papillary thyroid cancer (PTC) metastasize to regional nodal basins and the lungs. Visceral metastases are rare, but the involvement of multiple sites has been reported so far. Liver metastases from differentiated thyroid carcinoma (LMDTC) are rare.We present the case of a patient with follicular variant of papillary thyroid carcinoma (FVPTC) unusually involving the liver. Bangladesh J. Nuclear Med. 22(2): 146-149, Jul 2019